2019
DOI: 10.1136/bjophthalmol-2019-314086
|View full text |Cite
|
Sign up to set email alerts
|

Compensation of retinal nerve fibre layer thickness as assessed using optical coherence tomography based on anatomical confounders

Abstract: Background/AimsTo compensate the retinal nerve fibre layer (RNFL) thickness assessed by spectral-domain optical coherence tomography (SD-OCT) for anatomical confounders.MethodsThe Singapore Epidemiology of Eye Diseases is a population-based study, where 2698 eyes (1076 Chinese, 704 Malays and 918 Indians) with high-quality SD-OCT images from individuals without eye diseases were identified. Optic disc and macular cube scans were registered to determine the distance between fovea and optic disc centres (fovea d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 52 publications
1
32
1
Order By: Relevance
“…Finally, as OCT is essentially an analysis of reflectance profiles, changes in retinal thickness do not confer information about which specific cellular structures are affected. This limitation was significant in the RNFL, as the main retinal arterioles and venules cause significant variability in thickness measurements 88 and may explain why we, along with another histological study, found the RNFL to be thickest inferiorly 44 as opposed to other studies which found the RNFL to be thickest superiorly [40][41][42][43] . The ambiguity of reflectance profiles in OCT is also evident in analysis of Henle's fibre layer which we kept as part of the ONL segmentation to maintain consistency with other studies and OCT auto-segmentation protocol, despite anatomically being part of the OPL.…”
Section: Limitationscontrasting
confidence: 72%
“…Finally, as OCT is essentially an analysis of reflectance profiles, changes in retinal thickness do not confer information about which specific cellular structures are affected. This limitation was significant in the RNFL, as the main retinal arterioles and venules cause significant variability in thickness measurements 88 and may explain why we, along with another histological study, found the RNFL to be thickest inferiorly 44 as opposed to other studies which found the RNFL to be thickest superiorly [40][41][42][43] . The ambiguity of reflectance profiles in OCT is also evident in analysis of Henle's fibre layer which we kept as part of the ONL segmentation to maintain consistency with other studies and OCT auto-segmentation protocol, despite anatomically being part of the OPL.…”
Section: Limitationscontrasting
confidence: 72%
“… 21 Although there was no statistical difference in diagnostic power, it may be more logical to use parameters reflecting the FDD and disc area rather than a constant of 3.4 mm. Additionally, different blood vessel positions may have different effects on each individual 22 , 23 ; however, this was ignored to construct an average normative database.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the previous approaches have used standardized definitions of the peripapillary sectors or quadrants for OCT-A analysis and do not account for anatomical individual variations in the relative positions between the optic nerve head and the fovea. These anatomical variations, which have been shown to affect the discriminative ability of peripapillary RNFL measurements in glaucoma, [40][41][42][43] are likely attributed to relative shifts in the positions of the nerve fiber bundles and could affect capillary measurements. An advantage of the focal approach is that we were able to use the actual VF losses at the test locations without averaging over a larger sector.…”
Section: Discussionmentioning
confidence: 99%